Analisis Strategi Promosi pada UMKM Social Enterprise (Studi Kasus Pascorner Cafe and Gallery) - Annisa Nurul Fildzah; Ira Dwi Mayangsari (Jurnal Komunikasi, 2018)
The culinary business of Micro, Small, Medium Enterprise (MSME) is nowadays the most promising business industry, especially in Bandung, West Java. The beginners believe that culinary business is easy to run. One of the beginners is Pascorner Cafe And Gallery. This special cafe is run by almost 90% ex-prisoner. However people still always underestimate its existence, but the founder believes that with the right promotion strategy, will erase those negative perception. The main goal of this study is to analyze and evaluate the promotion strategy applied by Pascorner and moreover to form an alternative way to support its former promotion strategy. The researcher applied a qualitative method combined with a case study approach. The research showed that Pascorner has been using tools are advertising, sales promotion, and public relation. Alternative promotion strategy formed by the researcher is using Dwi Sapta IMC Model, it could describe how the external and internal environment is and how the people opinion is, clearly and in detailKeywords: MSME, Social Enterprise, Promotion Mix, IMC Model Dwi Sapta